Edukasi Perawatan Payudara pada Ibu Nifas - Asrianti Safitri Muchtar; Ita Novianti (Lembaga Pengembangan Kinerja Dosen, 2025)
One of the problems during the postpartum period is swollen breasts or breast milk retention. The cause of breast milk dams is breast milk that is not released immediately, causing the breasts to swell. Breast care during the postpartum period is a necessity for mothers. Breast care during the postpartum period is very important to facilitate the release of breast milk. The government has made various efforts to increase exclusive breastfeeding. In this regard, health education about breast care is an effort to improve mothers' skills in breastfeeding and especially increase breast milk production. The aim of this activity is to provide knowledge and improve postpartum mothers' skills in caring for breasts and then carry out an evaluation of knowledge and skills before and after counseling. The stages consist of a pre-test, followed by a presentation of educational material using lecture methods and breast care practice on teaching aids, followed by a question and answer session and discussion then ending with a participant post-test. The results showed that there was an increase in the level of knowledge and skills of postpartum mothers regarding breast care after the counseling was carried out.